Polish Ophthalmic and Pediatric Society consensus statement on vision screening of school-age children - Bakunowicz-Łazarczyk, Alina; Zaleska-Żmijewska, Anna; Gotz-Więckowska, Anna; Jackowska, Teresa; Wrotek, August; Rakusiewicz, Klaudia; Hautz, Wojciech; Szaflik, Jacek (Klinika Oczna / Acta Ophthalmologica Polonica, 2023)
The most common cause of reduced visual acuity in children is uncorrected refractive errors. Unlike adults, the symptoms of various ophthalmic diseases and refractive errors in children can go unnoticed for a long time. Therefore, vision screening in children is an essential part of prophylactic procedures to immediate diagnose and treat refractive errors. The article presents the consensus of the Polish Ophthalmic Society and the Polish Pediatric Society on recommended eye examinations for school- age children.